2019
DOI: 10.1007/s11357-019-00098-8
|View full text |Cite
|
Sign up to set email alerts
|

Gastro-intestinal and oral microbiome signatures associated with healthy aging

Abstract: The human oral and gut microbiomes influence health via competition for a distinct niche in the body with pathogens, via metabolic capabilities that increase host digestive capacity and generate compounds engaged in signaling pathways and modulation of immune system functions. Old age alters our metabolic and regenerative capacity. Following recruitment of 65 human subjects in the age range of 70 to 82, we discerned healthy aging (HA) and non-healthy aging (NHA) cohorts discordant in the occurrence of one or m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(86 citation statements)
references
References 74 publications
1
73
0
Order By: Relevance
“…Recent studies show that aging alters the gastrointestinal microbiome in both human and animals. 63,64 Probiotic treatments may have an even more pronounced effect on hypertension and deleterious consequences of hypertension in older individuals, such as the progressive decline in the volume of memory-associated brain areas with age. 65 However, caution is advised when extrapolating these findings to humans because of the possible differences in the behavior of the animal and human gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that aging alters the gastrointestinal microbiome in both human and animals. 63,64 Probiotic treatments may have an even more pronounced effect on hypertension and deleterious consequences of hypertension in older individuals, such as the progressive decline in the volume of memory-associated brain areas with age. 65 However, caution is advised when extrapolating these findings to humans because of the possible differences in the behavior of the animal and human gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…No information regarding the potential role in fibrosis has been reported about the genera negatively associated with cardiac fibrosis in our study. However, they are more abundant in healthy subjects than in subjects with different pathological conditions [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms could account for the beneficial effects induced by the mitochondrial anti-oxidant. The impact of this microbiota profile on the gut’s mucosal integrity and the translocation of microbial cell wall components, like LPS from Gram-negative bacteria and other toxic metabolites, could be the potential mechanisms involved in the impact of the gut dysbiosis in the cardiometabolic consequences in the context of obesity [ 19 , 40 , 42 , 43 , 44 ]. Dysbiosis can affect the integrity of the gut barrier, due to abnormal or reduced numbers of mucous cell production, resulting in diminished mucus production and both enhanced permeability and transit of antigens [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence has revealed that the aging process is also tightly linked to the homeostasis of the intestinal microbiome [ 40 , 41 , 42 , 43 ]. Over a century ago, Élie Metchnikoff proposed that the onset of the aging process could be delayed by manipulating the intestinal environment with friendly bacteria [ 44 ].…”
Section: Probiotics For Anti-aging Reported From Research Modelsmentioning
confidence: 99%